The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/add.12105
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco dependence diagnosis and treatment in Veterans Health Administration residential substance use disorder treatment programs

Abstract: Most veterans in Veterans Health Administration substance use disorders residential treatment programs appear to use tobacco, yet only one in 10 receives a documented ICD-9 TD diagnosis and pharmacotherapy while in a substance use disorders residential treatment program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…However, the Guideline recommendation has not led to significant changes in clinical practice. Addiction treatment programs rarely provide tobacco treatment (Fuller et al, 2007; Gifford, Tavakoli, Wang, Hagedorn, & Hamlett-Berry, 2013; Hunt, Cupertino, Garretta, Friedman, & Richter, 2012; Knudsen, Studts, Boyd, & Roman, 2010). An analysis of the reasons for failure to treat tobacco use in addiction programs (Prochaska, 2010) focused on provider beliefs including assumptions that tobacco is less harmful than other drugs, and that continued tobacco use supports abstinence from other substances.…”
mentioning
confidence: 99%
“…However, the Guideline recommendation has not led to significant changes in clinical practice. Addiction treatment programs rarely provide tobacco treatment (Fuller et al, 2007; Gifford, Tavakoli, Wang, Hagedorn, & Hamlett-Berry, 2013; Hunt, Cupertino, Garretta, Friedman, & Richter, 2012; Knudsen, Studts, Boyd, & Roman, 2010). An analysis of the reasons for failure to treat tobacco use in addiction programs (Prochaska, 2010) focused on provider beliefs including assumptions that tobacco is less harmful than other drugs, and that continued tobacco use supports abstinence from other substances.…”
mentioning
confidence: 99%
“…We lacked any data regarding the prevalence of current smoking, which might have added to the generalizability of study findings. Only a third of the current smokers enrolled in VHA residential addiction treatment programs are reported to have a documented TUD diagnosis (Gifford et al, 2013) while about 50% of smokers in general population have tobacco dependence (or TUD). (Grant et al, 2004) These rates may be even higher among veterans (Wagner et al, 2007) and those with smoking-related chronic disease (Darville and Hahn, 2014; Kalman et al, 2005; Westmaas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the 2004-2006 NSDUH found that female veterans were twice as likely as male veterans to experience past-year severe psychological distress (14.5 vs. 6.5 percent; SAMHSA, 2007), and Weiner et al (2011) found that the association between a psychiatric diagnosis and suicide was greater for female than male veterans. Female veterans in the VA SUD outpatient treatment setting also had high prevalences of comorbid mental disorders, with 47.6% also having PTSD, 38.7% serious mental illness, and 31.9% major depressive disorder (Gifford et al, 2011). In addition, females who served in OIF/OEF and used large quantities of alcohol and drugs screened positive for PTSD more than those not using substances, and comparison of women screening positive versus negative for PTSD found only alcohol use predicting the PTSD status (Nunnink et al, 2010).…”
Section: Discussionmentioning
confidence: 99%